Organizational and Legal Problems of Involvement of Citizens in Ensuring Public Order in the Republic of Kazakhstan - ZHANKHAN, Nurbakhyt (Journal of Advanced Research in Law and Economics, 2018)
The problem of ensuring public order has always been one of the most relevant ones. Public order has great conceptual importance for any country because without law and order, the state itself disappears, as well as the organization of society. This issue has always been relevant, and it has received significant attention of practitioners and academics. As practice shows, improving the efficiency of ensuring public order can be achieved through closer cooperation between the police and the civil society institutions and citizens emerging in the country. The article analyzes the legal foundations, forms and types of participation of citizens in ensuring public order. As an example, the positive experience of the reorientation of the police of foreign countries is reviewed. Based on the analysis, a conclusion was made about the necessity of accepting a number of organizational models used in some foreign countries, as well as changes in the law on the participation of citizens in ensuring public order.